Penggunaan Alat Bantu Dengar Terhadap Kemampuan Komunikasi Anak Tunarungu Di Sekolah Dasar Sinar Indonesia - Resita Chairunnisa, Adya; Kurniawaty, Lia; Kasih, Delina (INTELEKTIUM, 2025)
The Use of Hearing Aids on the Communication Skills of Deaf Children at Sinar Indonesia Elementary School. Thesis. Bekasi: Universitas Panca Sakti Bekasi. 2025. This study aims to investigate the effect of using hearing aids on the communication skills of deaf children at Sinar Indonesia Elementary School. The research employed a qualitative method with a case study approach. The research subjects included a deaf child with special needs who uses hearing aids, the classroom teacher, and the school environment as supporting factors. Data were collected through observation, interviews, and documentation. The findings indicate that consistent use of hearing aids provides significant positive effects. First, the child showed increased awareness of sounds, such as responding to the teacher’s call or the school bell. Second, the ability to understand simple instructions and conversations improved, which enhanced participation in group activities. Third, there was a noticeable increase in self-confidence and social skills, as seen in the child’s courage to greet, answer questions, initiate short conversations, and engage in group play. Fourth, supporting factors contributing to this success include consistent use of hearing aids, family support in ensuring optimal function, an inclusive school environment, and flexible teaching approaches by the teacher. In conclusion, this study confirms that hearing aids play a major role in enhancing the communication abilities of deaf children. However, their effectiveness is strongly influenced by the support of families, teachers, and the school environment. Therefore, collaboration among all parties is essential to optimize the communication and social development of deaf children.